Tobacco use behaviors and views on engaging in clinical trials for tobacco cessation among individuals who experience homelessness - Joshua Miller; Jordan Cuby; Sharon M. Hall; Maxine Stitzer; Margot Kushel; Donna Appiah; Maya Vijayaraghavan (Contemporary Clinical Trials Communications, 2023)
Background: Clinical trials that include contingency management for smoking cessation have shown promising results for short-term quitting, but none have explored this approach for long-term abstinence in people experiencing homelessness. We designed a clinical trial of an extended contingency management intervention for smoking cessation for people experiencing homelessness. This study has two aims: (1) to explore tobacco use behaviors, and views toward smoking cessation, and (2) to explore factors influencing acceptability of engaging in such a trial in a sample of adult smokers experiencing homelessness. Methods: We administered a questionnaire to obtain information on tobacco use behaviors and conducted in-depth, semi-structured interviews with 26 patients who had experienced homelessness and were patients at a safety net health clinic in San Francisco, California, where we planned to pilot the intervention. We obtained information on triggers for tobacco use, prior cessation experiences, attitudes toward cessation, attitudes toward engaging in a clinical trial for cessation, and factors that might influence participation in our proposed contingency management clinical trial. We analyzed transcripts using content analysis. Results: Participants described the normative experiences of smoking, co-occurring substance use, and the use of tobacco to relieve stress as barriers to quitting. Despite these barriers, most participants had attempted to quit smoking and most were interested in engaging in a clinical trial as a method to quit smoking. Participants noted that desirable features of the trial include: receiving financial incentives to quit smoking, having a flexible visit schedule, having the study site be easily accessible, and having navigators with lived experiences of homelessness. Conclusion: A patient-centric clinical trial design that includes incentives, flexible visits and navigators from the community may increase feasibility of engaging in clinical trials among individuals experiencing homelessness.